2018
DOI: 10.14198/jhse.2018.132.17
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the effectiveness of the use of instep weights (Powerinstep) in everyday runners

Abstract: The use of weights when training is very common, especially in compensatory work and in performing supplementary exercises. A new type of weight appeared in the market in 2015 with the name of Powerinstep. It is a weight placed on the instep of athletes running shoes (Padullés & Rius, 2015). The goal of this study was to analyse the effectiveness of the use of these weights (Powerinstep) regarding the effect of biomechanical and certain athletic performance variables on two everyday runners groups with similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 1 publication
(1 reference statement)
0
3
0
Order By: Relevance
“…Several scientific studies conducted with instep weights show positive effects on the race, due to the unique influence of their placement specifically on the instep (allowing full ankle's mobility) without neither decreasing inter-muscular coordination nor altering the running technique, 3,16,17,18 by positively modifying performance during workouts (technique, strength, speed, endurance). Likewise, instep weight use implies athlete's proprioception changes, helping those athletes who perform exercises in an automated way with an ineffective technique to improve it.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several scientific studies conducted with instep weights show positive effects on the race, due to the unique influence of their placement specifically on the instep (allowing full ankle's mobility) without neither decreasing inter-muscular coordination nor altering the running technique, 3,16,17,18 by positively modifying performance during workouts (technique, strength, speed, endurance). Likewise, instep weight use implies athlete's proprioception changes, helping those athletes who perform exercises in an automated way with an ineffective technique to improve it.…”
Section: Discussionmentioning
confidence: 99%
“…8 Preliminary studies using video-graphic measurement on a 1% slope treadmill showed step frequency significant increase (+0.96%), Ankle dorsiflexion and maximum Ankle dorsiflexion during the second gait phase or swing phase, from toe to heel floor contact, especially when using a 200gram (g) weight. 18 In a small pilot test in triathletes (n=3) biomechanical parameters were analyzed during the race without instep weights and with 100g and 200g instep weights, on a 1% slope treadmill. Using 200g instep weights step frequency increased in a 0.96% (p=0.0225) and dorsal ankle flexion significantly reduced (right: -8.04%, p=0.0065; left: -18.7%, p=0.0176).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation